2015
DOI: 10.1108/ejtd-07-2014-0055
|View full text |Cite
|
Sign up to set email alerts
|

Strategic learning capability: through the lens of environmental jolts

Abstract: 2015),"A longitudinal, mixed method evaluation of self-awareness training in the workplace", If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Learning capability is an essential factor that improves firm's efficiency in competitive strategies and providing customer value in the modern markets (Santos-Vijande et al, 2012). Empirically, numerous studies have demonstrated the positive impacts of learning capability on firm's financial and market performances (Peris-Ortiz et al, 2018;Visser, 2016;Moon & Lee, 2015;Santos-Vijande et al, 2012;Goh et al, 2012;Tohidi, Seyedaliakbar, & Mandegari, 2012;Limpibunterng & Johri, 2009;Bhatnagar, 2006;Prieto & Revilla, 2006). Therefore, this study hypothesized that:…”
Section: Learning Capability and Performancementioning
confidence: 98%
See 1 more Smart Citation
“…Learning capability is an essential factor that improves firm's efficiency in competitive strategies and providing customer value in the modern markets (Santos-Vijande et al, 2012). Empirically, numerous studies have demonstrated the positive impacts of learning capability on firm's financial and market performances (Peris-Ortiz et al, 2018;Visser, 2016;Moon & Lee, 2015;Santos-Vijande et al, 2012;Goh et al, 2012;Tohidi, Seyedaliakbar, & Mandegari, 2012;Limpibunterng & Johri, 2009;Bhatnagar, 2006;Prieto & Revilla, 2006). Therefore, this study hypothesized that:…”
Section: Learning Capability and Performancementioning
confidence: 98%
“…SMEs firm that successfully developed and continuously advances its ability in learning creates superior competitive advantage (Clements, 2010;Bhatnagar, 2006). Learning capability enable SMEs create the foundation for strategic learning, which facilitate adaptability and the attainment of competitive advantage (Santos-Vijande et al, 2012;Moon & Lee, 2015). Limpibunterng and Johri (2009) demonstrated that learning capability is a symbiotic to firm's innovation.…”
Section: Learning Capability and Performancementioning
confidence: 99%
“…In comparison, Prieto and Revilla (2006b) discovered a positive relationship between nonfinancial efficiency, financial performance and learning capacity. More recent research (such as Moon and Lee, 2015; Visser, 2016; Peris-Ortiz et al , 2018) have shown that learning skills have a positive effect on organizational financial and business outcomes.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Voronov and Yorks (2008) highlight the importance of power in strategizing. Strategic learning has been portrayed differently by various scholars as a social learning process (Burgelman, 1988; Eden and Ackermann, 2001), as strategic thinking (Casey and Goldman, 2010; Liedtka, 1998), as a strategic behavior design process (Kuwada, 1998) and as a firm’s higher-order learning process (Siren, 2012; Moon and Lee, 2015).…”
Section: Conceptual Frameworkmentioning
confidence: 99%